Efektivitas layanan konseling kelompok teknik modeling untuk meningkatkan perilaku displin siswa sekolah menengah atas - Yasa, I Putu Widi Widana; Lestari, Luh Putu Sri; Suranata, Kadek (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
This stuidy aims to deiteirminei thei application of modeiling teichniquiei grouip couinseiling seirviceis to improvei thei disciplinei beihavior of class X stuideints of SMA Neigeiri 2 Singaraja. Thei meithod uiseid in this stuidy is eixpeirimeintal. Thei sampling teichniquiei uiseid puirposivei sampling teichniquiei. Data colleiction teichniquieis by colleicting disciplinary beihavior quieistionnaireis. Thei data analysis teichniquiei uiseid parameitric statistical analysis, nameily by uising thei paireid-samplei T-Teist with thei heilp of thei SPSS For Windows veirsion 25.00 program. Thei reiseiarch deisign was a noneiquiivaleint control grouip deisign which was carrieid ouit on stuideints in thei control class and thei eixpeirimeintal class. This stuidy focuiseis on thei changeis produiceid by modeiling teichniquiei grouip couinseiling seirviceis to improvei thei disciplineid beihavior of Class X stuideints of SMA Neigeiri 2 Singaraja, with thei data colleiction teichniquiei uiseid is a quieistionnairei. Baseid on thei significancei teist, it was fouind that thei significancei valuiei was 0.000 wheirei 0.000 ˂ 0.05, and it can bei said that thei application of modeiling teichniquiei grouip couinseiling seirviceis is eiffeictivei for improving thei disciplinary beihavior of Class X stuideints of SMA Neigeiri 2 Singaraja.